Multiple abnormalities in a child with partial duplications of 10p and 13q from a 3:1 segregation of a maternal t(10;13) translocation. Issue 3 (March 1990) - Yip, M Y; Williams, J; Goddard, A; Campbell, P; Lambert, I; Smithells, R W
Abstract : Partial duplications of 10p and 13q in association with partial deletions of other chromosome segments have been variously reported. We describe here a female child with multiple congenital abnormalities and combined partial duplications of 10p and 13q resulting from a 3:1 segregation of a maternal t(10;13)(p13;q22). In comparing the phenotypic features of the two chromosome imbalances, the expression of features typical of partial duplication 10p appeared more pronounced.